Achievements and implications of HIV prevention programme among uniform service personnel: a systematic evaluation of HAF II project in Kogi state, Nigeria - Adelekan, Ademola L.; Musa, Gabriel; Aliyu, Hamza; Obinatu, Remi; Shaibu, Williams; Adah, Patrick; Adeoye, Segun; Olugbile, Michael; Adegoke, Temilade; Olaleye, Oladipupo S.; Omoregie, Philomena; Sani, Aliyu; et al. (International Journal Of Community Medicine And Public Health, 2017)
Background: Considering HIV pandemic among uniform service personnel (UPS), a lot of HIV intervention programmes designed to mitigate the spread have not been very successful thus the introduction of the HIV minimum prevention package intervention (MPPI). This paper therefore presents the achievements of HIV prevention programme among UPS in Kogi State, Nigeria including its implications for programming. Methods: This project was implemented among uniform service personnel who are in army, police, custom and prison in Kogi State. A total of 2676 was an estimated sample size for this intervention and MPPI was used for implementation of project activities. Data were entered on DHIS2 platform and later exported and analyzed using Microsoft Excel. Results: Out of the total number of 67 community dialogues/advocacies carried out during the project period, 56.7% were done in 2014 and a total of 187 participants participated with a participating rate of 62.0% and 38.0% in 2014 and 2015 respectively. The total number of condoms distributed during the entire project was 7,387 and 3038 peers were registered during the project. A total of 82.6% and 71.6% were reached with HIV counselling and testing and MPPI respectively while the prevalence of HIV was 5.3%. Conclusions: This intervention successfully scaled-up demand creation for condoms and HIV counselling and testing among uniform service personnel. More engagement at all levels to engender political commitment and ownership of the HIV response with a view of ensuring sustainability through increased funding should therefore be encouraged.